Effect of maltodextrin and zinc oxide nanoparticles on biomass and yield in cucumber - Ucan Tucuch, Omar; Betancourt Galindo, Rebeca; Juárez Maldonado, Antonio; Sánchez Vega, Miriam; Sandoval Rangel, Alberto; Méndez López, Alonso (Ecosistemas y Recursos Agropecuarios, 2024)
Climate change and population growth demand the search for new and innovative alternatives to improve the growth and production of crops based on a sustainable agriculture system. The aim of this work was to study the biostimulant effect of maltodextrin and zinc oxide nanoparticles on biomass and yield parameters of cucumber. The experiment was established under a randomized complete block design with a 5X2 factorial arrangement, with eight repetitions. The treatments consisted of four biostimulants and a control treatment and two application routes (foliar and drench). The biostimulants evaluated were pure maltodextrin, refined maltodextrin, zinc oxide nanoparticles alone and coated with maltodextrin, applied at 1000 ppm. Variables of fresh and dry aerial weight, fresh and dry root weight, number, weight, polar diameter and equatorial diameter of the fruit were measured. The results indicate that pure and refined maltodextrin increased aerial dry weight by 26.74% and 23.30%, respectively, when applied by foliar application. In addition, the application of maltodextrin via foliar increased the number of fruits by 31.56%, while the zinc oxide nanoparticles via drench by 32.39%. The route of application of the biostimulants had a significant impact on the aerial dry weight, number of fruits, polar diameter of the fruit and equatorial diameter of the fruit. Both maltodextrin and zinc oxide nanoparticles, in both presentations, showed positive biostimulant effects on the biomass and quality of cucumber fruits.
Keywords: bioestimulants; MDP; MDX; NPZnO; NPZnO-MDX